PHYSICAL DIAGNOSTICS AND WAYS OF DECLINE OF LINEAR RESISTANCES, INDUCTANCES AND CAPACITIES OF BAGATORIVNEVOI ROZVODCI OF SUBMICRON STRUCTURES OF LARGE-SCALE ARRAYS - Атаманюк, Роман Богданович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The basic tendency of modern microelectronics is reduction of sizes of elements of structures of VIS to the submicron topology sizes, that is transition to nanoelectronic - to the structures and elements with the sizes of nanometres. A raster electronic microscopy remains a basic diagnostic method which is used on all design times and making of submicron structures. REM allows to measure surface structures with high settling ability 2Ч10-3-2Ч10-2 mcm, to look after topographical and composition heterogeneities with spatial settling ability 5Ч10-2 mcm, to determine descriptions and defects of submicron p-n- transitions with locality 5Ч10-2 mcm on a depth less after 1 mcm. The size of contacts metal/semiconductor depends on different parameters of the system: works of lunge, superficial concentration of alloying admixture, type of conductivity of Si-pidcladoc, cleanness of surface of Si-plates before besieging of metal. For submicron technology both new materials and technologies and new contact structures, which successfully decide the problem of decline of contact resistance, and also problem of minimization of formation of hillocks are offered, which practically determine corrosive firmness of metallization.